Strengthening the Ties that Bind: Preventing Corruption in the Executive Suite - Bishara, Norman D. (Journal of business ethics, 2009)
High-profile corporate scandals earlier in this decade provoked outrage and legislative action; however, corporate executive-level ethical lapses continue to come to light. This article examines the work of Professor Dunfee and his coauthors on corruption, ethical leadership, and social contracts theory, and relates that literature to corrupt activities by corporate executives. Corruption is defined broadly to encompass executive self-dealing, which harms their firms. The specific example of stock options backdating is used to show the harmful impact on shareholders and the lack of managerial integrity though consequentialist, deontological, and legal analysis, as well as a critique of the practice using social contracts principles. Ultimately, this article utilizes the insights of Dunfee and his coauthors, and the lessons from the backdating example, to propose a framework aimed at improving corporate governance and preventing future executive corruption. The framework includes a strategy of identification and prevention, employing detection and eradication mechanisms, and institutional learning from past instances of corporate corruption.